Paediatric non-endemic nasopharyngeal carcinoma: our experience at an Indian tertiary teaching hospital - Khushboo Shrivastava; Lucky Sriwastwa; Priyanka Shrivastava; Tirumala Kanakadurga Sripati; Rajiv Kumar Jha (Student's Journal of Health Research, 2023)
Introduction: Nasopharyngeal carcinoma (NPC) is a very uncommon malignant tumour in children under the age of 20. The diagnosis of paediatric NPC is challenging due to its relative rarity. This unusual occurrence is frequently linked to delayed diagnosis, which can result in advanced loco-regional illness. Here, we investigate the clinical manifestations, investigations, and treatment of paediatric nasopharyngeal carcinoma in a nonendemic region. Method: The data from children and adolescents who had been diagnosed with nasopharyngeal cancer served as the basis for this study, which was carried out at the Cardiology and Pathology Departments of a tertiary teaching hospital in the eastern region of India. Result: In this retrospective analysis, 17 paediatric patients under the age of 18 were enrolled. Between December 2020 and January 2022, they were treated at a tertiary teaching hospital. 17 kids with nasopharyngeal cancer between the ages of 6 and 18 took part in this study. In this study, there were 7 girls (41.1%) and 10 boys (58.8%). NPC diagnosis occurred at a median age of 14 years (interquartile range: 6-18 years). In 15 (88.2%) individuals, neck swelling was the most frequent clinical manifestation, followed by nasal bleeding, nasal block, and hearing impairment in 10 (58.8%), 12 (70.5%), and 11 (64.7%) of cases, respectively.  Conclusion: With the exception of individuals who have distant metastatic disease, children with NPC have a very good prognosis. NPC in children is typically not clinically suspected until the patient is in a late stage. The most important prognostic factor is the TNM staging. Unfortunately, NPC frequently has distant metastases at the time of diagnosis in the paediatric age range and has a tendency to be locally progressed.